Public Relations Crisis Communication of Surabaya Shipping Polytechnic in Post-Crisis Image Recovery - Hilza Yudistira; Rheiza Whisnu Ramadhianti (Jurnal Pendidikan Indonesia, 2025)
In a crisis that occurs in an organization, PR is an important functional organization that bridges communication between the organization and the public. It is the main task and function of Public Relations to be able to overcome a crisis that affects the institution. This research uses descriptive qualitative methods. The results of this study show that in maintaining the image of the crisis issue that occurred, it is divided into four stages. The first is the Denial stage, where the Public Relations of the Surabaya Shipping Polytechnic denies by providing the postitive information side of the institution/organization so that not only negative information becomes the main statement. Second Evasion of Responsibility by convincing that the organization does not intend to do negative things and fully supports the running of a fair legal process regarding the crisis issue that occurred. Third Reducing Offensiveness, convincing the public that in addition to the negative crisis that occurred, there are still positive actions that have been taken in the past and can be well received by the public. Then the last stage is Corrective Action, which is to ensure that the crisis issues that occur can be handled properly so that it will not become a problem again in the future.